The Influence of Internal Integration on Operational Performance Through Supplier Integration at Pt Rotte Ragam Rasa (Rotte Bakery) Pekanbaru - Khilmi, Ariyanti; Samsir; Asrilsyak, Sharnuke (Program Pascasarjana, Universitas Riau, 2024)
This research aims to determine the effect of Internal Integration on Operational Performance through Supplier Integration at PT. Rotte Ragam Rasa Pekanbaru. The population in this study consists of the management and operational teams at PT. Rotte Ragam Rasa Pekanbaru, totaling 35 individuals. The sampling technique that will be used in this research is Non-Probability Sampling, specifically referred to as saturation sampling. This means that all 35 management and operational teams at PT. Rotte Ragam Rasa Pekanbaru will be included. Structural Equation Modeling (SEM) is the analytical method used in this research, processed using SmartPLS version 4.0. The results of the hypothesis test from this study indicate that Operational Performance is significantly and positively influenced by Internal Integration. Supplier Integration is significantly and positively influenced by internal integration. Operational performance is significantly and positively influenced by supplier integration. The influence of Internal Integration on operational performance is minimized by supplier integration.